Thermal parameters changes in males of Rhinella arenarum (Anura:Bufonidae) related to reproductive periods - Alfredo Sanabria, Eduardo (2011)
he regulation of body temperature in ectotherms has a major impact in their physiological and behavioral processes. Observing changes in thermal parameters related with reproduction allows us to better understand how Rhinella arenarum optimizes a thermal resource. The aim of this study was to compare the thermal parameters of this species between breeding and non-breeding periods. In the field, we recorded the body temperature from captured animals, the air temperature, and the temperature of the substrate. In the laboratory, we measured the temperature R. arenarum selected on a thermal gradient and the critical extreme temperatures. The results of our study show variations in thermal parameters between the two situations studied. This species makes efficient use of thermal resources during the breeding period by basking to significantly increase body temperature. Because calling is energetically costly for males, this behavior results in increased efficiency to callers during the breeding period. Rev. Biol. Trop. 59 (1): 347-353. Epub 2011 March 01.